How do Malawian women rate the quality of maternal and newborn care? : experiences and perceptions of women in the central and southern regions - Kambala, Christabel; Lohmann, Julia; Mazalale, Jacob; Brenner, Stephan; Allegri, Manuela De; Muula, Adamson S.; Sarker, Malabika (© 2015 BMC Pregnancy & Childbirth, 2016)
Includes bibliographical references (page 18-19).